Practical fiber optics - Bailey, David (Telecommunications engineer) (Elsevier, 2003)
Readers will use this knowledge to develop the required techniques for design, installation and maintenance of their own fiber optic systems. * Ideal for those with some background in communications but without previous knowledge of fiber optics * Provides a comprehensive treatment of the fundamentals of fiber optic systems and their individual components * Places emphasis on practical techniques of component installation and system design.